THE EFFECT OF PROFITABILITY AND LIQUIDITY ON CAPITAL STRUCTURE WITH FIRM SIZE AS MODERATING VARIABLE - Kho, Angelina Richie; Susanti, Merry (Graduate Program of Universitas Tarumanagara, 2023)
This study aimed to obtain the empirical evidence of the effect of profitability and liquidity on capital structure with firm size as a moderating variable. The study was conducted on manufacturing companies listed on Indonesia Stock Exchange for the 2018-2020 period and sample obtained through purposive sampling technique were 58 companies after outlier being eliminated. Data analysis method used in this study were multiple regression and moderated analysis regression. The statistical tool used for data processing in this research was EViews 9. The results of this study were (1) profitability had a negative and significant effect on capital structure, (2) liquidity had a negative and significant effect on capital structure, (3) firm size was not able to moderate the effect of profitability on capital structure, (4) firm size was not able to moderate the effect of liquidity on capital structure.